Political and Social Commentary in Contemporary English Drama: Angels in America by Tony Kushner, the History Boys by Alan Bennett and the Crucible by Arthur Miller - Ali, Shakir Hussein (Integrated Journal for Research in Arts and Humanities, 2024)
For centuries, dramatists have utilized the powerful aspect of theatre to offer perceptive analyses of societal happenings and, in the process, cause a lot of positive changes in man and his environment. This essay discusses this fact by citing Tony Kushner's Angels in America, Alan Bennett's The History Boys, Arthur Miller's The Crucible, and Tony Kushner's Angels in America, drawing upon Levinas and Benjamin's theories, Kushner's political play. This article shows how the three works examples of books about people, events, or society at large are provided by Tony Kushner's Angels in America, Alan Bennett's The History Boys, and Arthur Miller's The Crucible portray the social and political context in which they were written through symbolism, metaphor, and sometimes even a straightforward comparison. These three plays are forecasting because they are both allegories for the times they were written for and have a contemporary interpretation. Each of the three plays addresses a different aspect of society and politics while also addressing the human condition.